Predicting CTCF-mediated chromatin interactions by integrating genomic and epigenomic features - Yan Kai (Nature Portfolio, 2018)
CTCF mediates long-range chromatin interactions which are important for genome organization and function. Here, the authors demonstrate that CTCF-mediated interactome exhibits extensive plasticity and present Lollipop, a machine-learning framework which predicts CTCF-mediated long-range interactions using genomic and epigenomic features.